Politics, philosophy, and humor at the Byzantine court - Theodore II Lascaris, Bizans İmparatoru, 1222-1258. (Washington, DC)
xi, 223 sayfa
Keywords: “The thirteenth-century emperor Theodore II Laskaris, ruler of the Empire of Nicaea, is among those versatile authors of the Byzantine era who produced numerous little-known gems of literature and thought. He composed the sole theoretical work on friendship surviving from Byzantium, wrote philosophy with verve and humor, and was perhaps the most passionate advocate of the idea of a communal Hellenic identity in the Middle Ages. This volume represents the first translation into English of eight works by Laskaris. An introduction and annotations to the translations orient the reader and contextualize these fascinating pieces. The selections themselves include a satire of his tutor, his oration on friendship and politics, his oration on Hellenism, and philosophical works and musings that include a treatise filled with Socratic irony. They represent the most prominent strands of Laskaris's thought and provide the reader with a well-rounded portrait of this remarkable author“ --